Struggles over corporate social responsibility meanings in teaching practices: The case of hybrid problem-based learning. Issue 5 (November 2013) - García-Rosell, José-Carlos
Although experiential learning has been widely discussed in relation to the teaching of corporate social responsibility, the socially mediated and discursive nature of experiential learning approaches to corporate social responsibility has been either neglected or given only cursory coverage in the literature. Considering this gap, I problematise corporate social responsibility education within the axioms of managerialism, arguing that it should also allow business students to critically evaluate, analyse and question the basic premises underlying contemporary business practices. Using an action research approach, I explore the possibilities and challenges of using hybrid problem-based learning to help business students engage in critically reflexive processes and, thus, the social construction of corporate social responsibility meanings. Drawing on discourse analysis, I illustrate two central discursive patterns that characterise the struggle over corporate social responsibility meanings in a series of courses implemented in the business curriculum of a Nordic university between the years 2007 and 2010. The findings offer empirical support for several key arguments in the debate over corporate social responsibility education.